(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Describe the knowledge and practice of primary school teachers on injury prevention for students in Vinh city and identify some related factors in 2021. Subjects and research methods: Primary school teachers currently working at primary schools in Vinh city, Nghe An province, in 2021. Cross-sectional descriptive design of over 300 teachers at six primary schools in Vinh city by face-to-face interviews. Results: 84.0% of teachers have a general knowledge Pass and 69.0% practice Pass on the achievement of ICT for primary students. Teachers with good knowledge of IAD are 2.5 times more likely to have practice than teachers with poor knowledge (OR=2.5; CI: 1.4-4.8). Teachers who were trained in IAD were 2.8 times more likely to know teachers who were not trained (OR=2.8; CI: 1.1–6.8). Conclusion: The organization of training and propaganda for teachers plays an important role in the prevention of accidents and injuries and should be paid more attention to by schools.